Long-term Outcomes of Short-Stem Total Hip Arthroplasty in Patients Aged Forty Years or Younger with Osteonecrosis of the Femoral Head - Tippimanchai, Thanut; Suksathien, Yingyong; Sueajui, Jithayut; Lajuntuk, Bankchart; Khamphaeng, Sirawitz (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: This study aimed to analyze the clinical and radiographic results with a minimum 10-year follow-up of short-stem total hip arthroplasty (THA) in patients aged 40 years or younger with osteonecrosis of the femoral head (ONFH). Methods: A retrospective analysis was conducted on 45 of 55 eligible patients with ONFH who underwent Metha® short-stem THA, with a minimum 10-year follow-up (82% follow-up rate). The clinical outcomes were measured using the Harris Hip Score (HHS) and Forgotten Joint Score (FJS). Radiography was used to assess osteointegration, stem subsidence, and stress shielding. Patient satisfaction was recorded. Results: The mean HHS significantly improved from 43.2 preoperatively to 97.4 at the final follow-up (p<0.0001), and the mean FJS score was 93.4. Radiography revealed osteointegration mainly in zones 1 (95.6%), 2 (88.9%), 6 (100%), and 7 (91.1%). The patient satisfaction was ‘very satisfied’ in 43 (95.6%) and ‘satisfied’ in 2 (4.4%) patients. The Kaplan-Meier survivorship for the overall implant system was 93.3% at 10 years, with revisions required in 3 cases (acetabular component or liner only). At 10 years, stem survivorship was 100% for any reason and 100% for aseptic loosening. Conclusions: Short-stem THA provides promising long-term clinical outcomes for patients aged 40 years or younger with ONFH. Radiographic results demonstrated physiological proximal load transfer with minimal stress shielding.